Digitalisasi Layanan Pendidikan Bisnis: Adaptasi Kampus dan Lembaga Pendidikan terhadap Educational Teknologi - Mawdatul Khairia, Fiyasti; Saragih, Nadia; penggabean, susi (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
Digitalization has become the primary catalyst in transforming business education services in the era of information technology. This article explores how universities and educational institutions adapt to the development of educational technology to enhance both the quality of learning and operational efficiency. Employing a descriptive-qualitative approach based on various literature sources, this study highlights significant shifts in online learning systems, digital academic administration, and the integration of technology into the business education curriculum. The findings indicate that institutional adaptation and the role of educational entities in digitalization facilitate the delivery of more flexible, measurable, and industry-relevant educational services. Nevertheless, challenges such as the digital divide, human resource readiness, and the need for institutional policy frameworks continue to hinder the optimal use of educational technology. This study underscores the importance of inter-institutional collaboration in building a responsive and sustainable digital business education ecosystem